The pCONus device for the endovascular treatment of wide neck bifurcation aneurysms. (7th September 2015) - Lubicz, Boris; Morais, Ricardo; Alghamdi, Faisal; Mine, Benjamin; Collignon, Laurent; Eker, Omer Faruk
Abstract : Background and purpose: The pCONus is a new stent featuring a distal end that opens like a blossoming flower with four petals. The device is implanted in the aneurysm sac at the level of the neck. We report our initial experience in a series of patients treated with this device. Methods: This retrospective study was approved by the authors' ethics committees. 18 patients with 19 unruptured wide neck bifurcation intracranial aneurysms (IA) were treated by pCONus placement and coiling. Technical issues, immediate post treatment angiographic findings, and clinical and imaging follow-up were assessed. Results: Embolization was successful in all patients. There were 11 women and 7 men with a mean age of 60 years. Median aneurysm size was 9 mm (range 5.5–25 mm). The device was precisely placed and detached in all cases, allowing for subsequent coiling. Two patients experienced a symptomatic complication, one of which, a thromboembolism, was related to the use of the pCONus. This patient had a slight hand paresis. 16 patients had a normal neurological examination at discharge. Immediate anatomical results were 13 complete occlusions, 2 neck remnants, and 4 incomplete occlusions. Imaging follow-up was obtained in 12 patients (mean 9.5 months, range 2–24 months) and showed 9 stable occlusions and 3 recanalizations, of which 2 were retreated. Conclusions: In this initial series of patients, endovascular treatment of wide neck bifurcation IAs with the pCONus was feasible, with acceptable clinical and anatomical outcomes. Further studies are needed to evaluate the indications, safety, and efficacy of this new device.